A mathematical modeling approach to assess biological control of an orange tree disease. (August 2021) - Bulai, Iulia Martina; Esteves, Ana Cristina; Lima, Fernanda; Venturino, Ezio
Abstract: The model presented and investigated here describes the interaction between the orange tree and two different microorganisms, the pathogen fungus Guignardia citricarpa and the antagonist Trichoderma harzianum T1A . The pathogen-free point and coexistence are the only possible system's equilibria. The pathogen-free point bifurcates from coexistence when the antagonist strength is sufficiently high, but does not appear to be much dependent on the amount of beneficial fungus employed. This result represents a relevant guideline for the applied ecologist and for the farmers. Sensitivity analysis in suitable parameter spaces is performed numerically.